Development And Effectiveness Of Mass Media Education Campaign On The Knowledge, Beliefs, Attitudes And Behaviour Relating To Qat Chewing And Health Risk Among Secondary School Students In Aden, Yemen - Al-Kaf, Mohammed Saleh Ahmed (2017)
Qat (Catha edulis) is a species belonging to the plant family Celastraceae. Qat is commonly chewed throughout East Africa and the Arabian Peninsula since the 11th centuryThe fresh leaves and buds of the plant contain cathinone and cathine as the active substances. Cathinone is an amphetamine like stimulant responsible for most of its pharmacological action. Among them, is enhancing concentration, and this has been used as a reason for the students to consume qat. A cross-sectional study was carried out aimed at determining the prevalence of qat chewing among adolescents followed by a pre-test post-test experimental control design study aimed at evaluating the outcome of mass media educational campaign on the knowledge, beliefs, attitudes and behavior of qat chewing health risk among public secondary school students in Aden city, Yemen.